Digitalisasi Media Sebagai Upaya Branding Wisata Sendang Growong Desa Sumbersawit Kabupaten Magetan - Linggar Sasongkowati; Mara Salsabila Makaroda; Pratiwi Anjar Sari (PT. Intelek Cendikiawan Nusantara, 2024)
Community Service Program (KKN) is the real evidence of the implementation of the Tri Dharma of Higher Education namely in the aspect of community service. Through KKN activities in Sumbersawit Village, Sidorejo sub-district, Magetan regency. This article aims to explain the role of KKN students from Sebelas Maret University in branding and promoting sendang growong tourism in Sumbersawit village. Student used a qualitative research method with a descriptive approach was used in this study because it can help researchers collect and analyze data more comprehensively. The results showed that this tourist attraction has the potential to be developed for the better so that it can have a positive impact on the aspects of life of the surrounding community. The development steps taken are through branding and promotion. SWOT analysis is used as one of the methods to design a promotion strategy that will be carried out. Creating a logo, initiating the creation of original marchendais, is the target of this research. This activity aimsto improve the brand image of Sendang Growong and intoduce it to the wider community.